Study of Development of First Aid Training Curriculum for Disaster and Emergency First Responders in Disaster Management Institute of Indonesia (DMII) Aksi Cepat Tanggap (ACT) - Ujang Dede Lasmana; Fevi Wahyu Fitriana; Harries Madiistriyatno (International Journal Labs, 2024)
Indonesia is a region with a high number of disasters, so emergency preparedness is needed to minimize the number of deaths and increase efforts to save lives. Apart from disasters, events that cause emergencies can also be caused by social and cultural conditions. Indonesia is a country with a high level of diversity (both religious, cultural, social and political views) which can pose a threat to life-threatening emergencies. Life-saving measures on the front lines of disaster areas and areas affected by emergencies can take the form of pre-hospital aid measures, and for this we need people who have pre-hospital life saver (PHLS) skills. The aim of this study is to identify a competency and self-efficacy based pre-hospital assistance skills training curriculum for disasters and other emergencies for the community that can be implemented in Indonesia. The method used in this study is a combination of analytical qualitative literature review with the findings or experiences of researchers when carrying out the task of providing pre-hospital help services and training. The results of this research are: first, a training curriculum is needed to ensure that training graduates have competence and also have high self-efficacy; second, the training material consists of knowledge and skills to save lives and prevent disability in sufferers; third, it is necessary to create a pre-hospital aid manual for trained lay people; and fourth is the need for pre-hospital aid training to be held throughout Indonesia, especially in disaster and emergency prone areas.